HUBUNGAN ANTARA PERANAN PENYULUH DENGAN PARTISIPASI ANGGOTA DALAM KEGIATAN KELOMPOK TANI DI KECAMATAN BANYUDONO KABUPATEN BOYOLALI - Arip Wijianto (AGRITEXTS: Journal of Agricultural Extension, 2008)
The aim of this research is to find out the correlation between the extensioner 's role and the Member's participation in the farmer 's group activities. In accordance with the aim ofthe study, this research applies survey method with descriptive correlation type. The population of the study are th farmers who become a member offarmer 's group in the District of Banyudono. 50 farmers are taken as the samples ofthe study by using multi stage cluster random sampling. The data collecting technique is questionnare methode for all ofthe instruments. The analysis result at 5% level ofsignificance show that there is significant correlation between the extensioner 's role And the Member's participation in the farmer's group activities ( rxyl = 0,561 > r,ab = 0,279 ).